Preliminary results on estimation of the dispersive dielectric properties of an object utilizing frequency-dependent forward-backward time-stepping technique - Ng, Shi W.; Kismet, Anak Hong Ping; Shafrida, Sahrani; Mohammad Hamiruce, Marhaban; Mohd I., Sariphan; Toshifumi, Moriyama; Takashi, Takenaka (Electromagnetics Academy, 2016)
In this paper, a Frequency-Dependent Forward-Backward Time-Stepping (FD-FBTS) inverse scattering technique is used for reconstruction of homogeneous dispersive object. The aim of the technique is to reconstruct the relative permittivity at infinite frequency, static relative permittivity and static conductivity of the homogeneous dispersive object simultaneously. The technique utilizes iterative finite-difference time-domain (FDTD) method for solving inverse scattering problem in time domain. The minimization of the cost functional is carried out utilizing Dai-Yuan nonlinear conjugate-gradient algorithm. The Fréchet derivatives of the augmented cost functional are derived analytically with respect to scatterer properties. Numerical results for reconstruction of two-dimensional homogeneous dispersive illustrate the performance of the proposed technique.